Pengaruh Sistem Informasi Akuntansi, Ukuran Kinerja Keuangan Dan Otoritas Pengambilan Keputusan Terhadap Akuntabilitas Kinerja - Novaliastuti Masiaga (Gorontalo Accounting Journal, 2019)
The purpose of this study is to examine the variables that affect the performance accountability of the Boalemo Regency government. Data collection was carried out by giving questionnaires to 30 OPDs in the local government of Boalemo Regency and also by interviewing several financial subdivisions. The statistical method used to test the hypothesis is and multiple linear regression.The results of the study show that. First, accounting information systems, measures of performance and decision-making authority have a positive effect on performance accountability. Second, information systems and decision-making authority partially have a positive and significant influence on performance accountability. Third, the measure of financial performance partially has a negative and insignificant effect on the performance accountability of Boalemo District Government agencies. It can also be seen from the Determination Test that 32% increase in the accountability performance of Buol district government agencies can be explained by accounting information systems decision making while the rest can be explained by other variables at 68%.